The Impact of Tiktok Shop Closure on Generation Z's Buying Interest - Yuningpra, Ghinareeshma Drana; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim :  This research is motivated by the official government closure of the latest feature of TikTok or the so-called TikTok Shop feature, since November 4, 2023. The closure of this feature is due to a prohibition contained in the Revision of the Minister of Trade Regulation number 50 of 2020 concerning Provisions for Business Licensing, Advertising, Coaching and Supervision of Business Actors in Trading Through Electronic Systems. Design/Methode/Approach:  This study aims to show the impact of closing Tiktok Shop on Generation Z's buying interest. This research is a qualitative study, where the main data is obtained from Tiktok Shop users who point to Generation Z. This research uses phenomonological phenomena as a research method to reveal the impact and phenomena experienced by Generation Z when searching for and meeting their needs. Research Finding:  The results of initial observations and data obtained from interviews of sources and opinions of generation z in the comment column of the Tiktok platform are, they feel very disappointed with the closure of this Tiktok Shop feature because in their opinion this feature really helps them to save expenses and facilitate shopping without having to open and close other social media platforms. Theoretical contribution/Originality : Buying interest can broaden understanding of the tendencies and passions that strongly drive a person to buy a product. Measure the impact and buying preferences of Generation Z on the TikTok Shop Platform and dig deeper into how impactful these TikTok Shop closures are on Generation Z's buying interest. Practitionel/Policy implication : This research provides practical implications for the TikTok platform about how much influence generation Z's buying interest has on the online shopping system and what aspects can influence that buying interest. Research limitation : This study only discusses the buying interest of generation z, as well as the impact experienced on closing TikTok Shop